Benchmarking Public-Private Partnerships Procurement 2015 : A Pilot in 10 Economies - World Bank Group (World Bank, Washington, DC, 2019)
Inadequate infrastructure in developing countries is a major constraint on growth. Many governments face the challenge of low quality or non-existent infrastructure, often deriving from insufficient funding, poor planning, or ineffective delivery and maintenance. Public-Private Partnerships (PPPs) can help improve the quality of infrastructure "by vesting control rights with the private sector, bundling into one contract the design, construction, operation, and maintenance of the facility, and by transferring the risk of cost and time overruns to the private partner". Well-structured PPPs create the right incentives to maintain high performance records. They also tend to realign incentives in long-term service contracts so that responsibility for service delivery is transferred to the party with most to gain from sustained high performance. An appropriate PPP preparation and bidding process leads to a more efficient use of resources because the private partner will have a stake in the long-term implications of the cost of the infrastructure. In addition to these benefits, PPPs offer an opportunity to conduct "more informed and realistic selection procedures" by assessing long-term commitments and risk and shifting the focus from inputs to outputs (and even outcomes)